Thazha Varkey Paul, The Warrior State: Pakistan In The Contemporary World - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2015)
Professor T.V. Paul’s short book on Pakistan is an attempt to understand Pakistan’s identity as a state. The study examines how the nation that came into existence seeking to be a welfare state became a garrison state with the single point agenda of protecting national security. Prof. Paul contends that, like resource rich (oil-rich) countries are experiencing a "resources curse," Pakistan is facing a "geostrategic curse" which prevents it from establishing a strong democracy, and focus on economic development. The author opines that Pakistan’s policies based on “hyperrealpolitik” view of the outside world, have backfired. The book’s main argument revolves around the question how the Pakistani elites have sought economic and military benefits accruing from its geostrategic position. The author has compared Pakistan with some other countries that have overcome problems of economic development and security. T.V. Paul is James McGill Professor of International Relations in the Department of Political Science at McGill University, where he has been teaching since 1991. He specializes in international relations, especially international security, and South Asia. He is the author/editor of 15 books and has published a large number of articles and book chapters.